MEDIA SOSIAL SEBAGAI PENDUKUNG JARINGAN KOMUNIKASI POLITIK - Eko Harry Susanto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2017)
Communication and information technology development makes it easier for interaction between individuals and groups. Message and news traffic are not fully controlled by the state, but are free to flow to public. Therefore, social media that have power to disseminate information, be an option to influence, motivate, and perform actions desired by message spreaders. At the same time, dominance of mainstream mass media is fading away. This study aims to: (1) describe social media users without socioeconomic and political differences, (2) analyze social media and mass media efforts to reach audiences, (3) observe social media as a supporter of political communication networks in democracy state. This study, using qualitative methods to provide a holistic picture of social media in relation to the political communication network utilized by individuals, groups and various political entities. The results of this study are, users of social media are not bound by social, economic and political status;  Social media and mainstream mass media have different characters in spreading messages to audiences; And social media is a supporting of political communication network in democracy of the state.